Development of a psychological management intervention protocol for colorectal cancer patients: a Delphi study on benefit finding - Linzhi Jiang; Rongrong Liu; Fan Wang; Xingqun Tan; Liyuan Sun (PLoS ONE, 2025)
Objective This study aimed to develop Benefit Finding intervention protocols for colorectal cancer patients on psychological management in China. Methods We created an initial draft of such a protocol through a comprehensive literature review and group discussions. A two-round Delphi study via WeChat correspondence was conducted, with a group of 14 Chinese experts. Experts rated and scored the importance of indicators on a five-point Likert scale. Results The response rates for two rounds both were 100%(n=14), with an authority coefficient of 0.86. The mean value assigned to the importance of the items ranged from 4.07 to 5.00, with coefficients of variation between 0.00 and 0.17; the Kendall coefficient was 0.214 (P<0.05). Ultimately, we established an index system comprising 8 primary items, with respective weights of 0.133, 0.131, 0.122, 0.116, 0.129, 0.122, 0.124, and 0.124. Additionally, we identified 25 secondary items and 53 tertiary items. Conclusion This protocol demonstrates authenticity, objectivity, and broad applicability, providing a valuable reference for future psychological care and self-management strategies for colorectal cancer patients following surgery.